CAR-T cells targeting CCR9 and CD1a for the treatment of T cell acute lymphoblastic leukemia - Néstor Tirado; Klaudyna Fidyt; María José Mansilla; Alba Garcia-Perez; Alba Martínez-Moreno; Meritxell Vinyoles; Juan Alcain; Marina García-Peydró; Heleia Roca-Ho; Narcis Fernandez-Fuentes; Mercedes Guerrero-Murillo; Aïda Falgàs; et al. (Journal of Hematology & Oncology)
Abstract T cell acute lymphoblastic leukemia (T-ALL) is an aggressive malignancy characterized by high rates of induction failure and relapse, and effective targeted immunotherapies are lacking. Despite promising clinical progress with genome-edited CD7-directed CAR-T cells, which present significant logistical and regulatory issues, CAR-T cell therapy in T-ALL remains challenging due to the shared antigen expression between malignant and healthy T cells. This can result in CAR-T cell fratricide, T cell aplasia, and the potential for blast contamination during CAR-T cell manufacturing. Recently described CAR-T cells target non-pan-T antigens, absent on healthy T cells but expressed on specific T-ALL subsets. These antigens include CD1a (NCT05679895), which is expressed in cortical T-ALL, and CCR9. We show that CCR9 is expressed on >70% of T-ALL patients (132/180) and is maintained at relapse, with a safe expression profile in healthy hematopoietic and non-hematopoietic tissues. Further analyses showed that dual targeting of CCR9 and CD1a could benefit T-ALL patients with a greater blast coverage than single CAR-T cell treatments. We therefore developed, characterized, and preclinically validated a novel humanized CCR9-specific CAR with robust and specific antileukemic activity as a monotherapy in vitro and in vivo against cell lines, primary T-ALL samples, and patient-derived xenografts. Importantly, CCR9/CD1a dual-targeting CAR-T cells showed higher efficacy than single-targeting CAR-T cells, particularly in T-ALL cases with phenotypically heterogeneous leukemic populations. Dual CD1a/CCR9 CAR-T therapy may prevent T cell aplasia and obviate the need for allogeneic transplantation and regulatory-challenging genome engineering approaches in T-ALL.